PAIS/FAMÍLIA E OS CUIDADOS COM O RECÉM NASCIDO PREMATURO APÓS A ALTA HOSPITALAR - Busatto, Emanoele (2018)
Prematurity of newborns (NBs) is responsible for the greater number of hospitalizations in the Neonatal Intensive Care Units (NICUs), most often associated with a risk pregnancy. Objective: To construct a booklet with orientations to parents / family after discharge. Methodology: This action research was carried out in a NICU and an outpatient clinic at a mid-sized hospital in a city in the interior of Rio Grande do Sul. Results: A total of 14 professionals participated in the NICU, and nine parents / in the NICU. The professionals answered a questionnaire containing the guidelines of care with the NB after discharge from the ICU. In view of these guidelines, a booklet was prepared and distributed to the parents of newborns at discharge. From the questionnaires of the professionals emerged two categories: "General care with the health of the newborn after discharge from the ICU" and "Caring for the feeding of the mother who is breastfeeding". After this stage of the analysis of the results obtained from the questionnaires of the professionals, a primer was elaborated. This booklet was distributed to the parents / family at the time of the guidelines for ICU child discharge. Parents were asked to read carefully the guidelines so that on the first day of return in the outpatient clinic of the preterm, they could assess if the guidelines were sufficient. Subsequently, nine parents who were in the 1st consultation in the egress clinic participated in the evaluation of this booklet. From these evaluation interviews, two categories emerged, namely: "Preparing for discharge from the ICU"; "Parent 's main doubts and evaluation of the booklet". Final considerations: In the studies researched, it was possible to highlight the concern with health education for the families of hospitalized premature newborns, which deserves attention of the health teams in order to improve the routines of the services in this area and to promote discussions on the subject with the professionals of multiple formations, above all, of nursing because of its proximity to the clientele. Also, the use of educational materials in health orientation and education has obtained positive results, thus creating a reflection that the creation of educational materials can in fact contribute to the process of effective health education. Product and its applicability: The final product resulting from this research was a booklet with guidelines for parents / family, based on the discussions and ideas of professionals and parents / family. This brings the importance of the use of educational materials in health orientation and education, thus creating a reflection that the creation of educational materials can in fact contribute to the process of effective health education.